Nanobody-based CAR T cells that target the tumor microenvironment inhibit the growth of solid tumors in immunocompetent mice - Xie, Yushu Joy (Proc Natl Acad Sci U S A, 2019)
Chimeric antigen receptor (CAR) T cell therapy has been successful in clinical trials against hematological cancers, but has experienced challenges in the treatment of solid tumors. One of the main difficulties lies in a paucity of tumor-specific targets that can serve as CAR recognition domains. We therefore focused on developing VHH-based, single-domain antibody (nanobody) CAR T cells that target aspects of the tumor microenvironment conserved across multiple cancer types. Many solid tumors evade immune recognition through expression of checkpoint molecules, such as PD-L1, that down-regulate the immune response. We therefore targeted CAR T cells to the tumor microenvironment via the checkpoint inhibitor PD-L1 and observed a reduction in tumor growth, resulting in improved survival. CAR T cells that target the tumor stroma and vasculature through the EIIIB(+) fibronectin splice variant, which is expressed by multiple tumor types and on neovasculature, are likewise effective in delaying tumor growth. VHH-based CAR T cells can thus function as antitumor agents for multiple targets in syngeneic, immunocompetent animal models. Our results demonstrate the flexibility of VHH-based CAR T cells and the potential of CAR T cells to target the tumor microenvironment and treat solid tumors.